2022
DOI: 10.1186/s12884-022-04522-4
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depressive symptoms in rwanda: rates, risk factors, and social support

Abstract: Background Prevalence of perinatal depression is high in Rwanda and has been found to be associated with the quality of relationship with partner. This study extends this work to examine the relationship between antenatal depressive symptoms and social support across several relationships among women attending antenatal care services. Methods Structured survey interviews were conducted with 396 women attending antenatal care services in 4 health ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
4
9
0
Order By: Relevance
“…The mean of 10.84 ± 5.91 for the EPDS score indicates an elevated level of depressive syndromes within the studied population. These findings are consistent with other studies conducted in Rwanda, which showed a high prevalence of antenatal depressive symptoms [18,25]. Despite the elevated prevalence of maternal depressive symptoms, we did not find any statistically significant associations with childhood linear growth.…”
Section: Discussionsupporting
confidence: 92%
“…The mean of 10.84 ± 5.91 for the EPDS score indicates an elevated level of depressive syndromes within the studied population. These findings are consistent with other studies conducted in Rwanda, which showed a high prevalence of antenatal depressive symptoms [18,25]. Despite the elevated prevalence of maternal depressive symptoms, we did not find any statistically significant associations with childhood linear growth.…”
Section: Discussionsupporting
confidence: 92%
“…The high prevalence observed in this study is consistent with previous research conducted in Kenya, where the prevalence was 36% (21). However, these ndings are higher than those in Tanzania, where the prevalence was 11.5% (22), and in Rwanda, where it was 26.6% (23). This discrepancy could be attributed Different assessment tools may yield different prevalence rates due to variations in the way antenatal depression is measured.…”
Section: Discussionsupporting
confidence: 88%
“…Figure 2 shows the distribution of articles from Ethiophia, Kenya, Tanzania, Qatar, Nigeria, Thailand, Rwanda, and China. 0.81 0.37 1.81 (Duko et al, 2019) 2.14 1.49 3.11 (Keliyo et al, 2021) 3.34 1.50 7.43 (Lodebo et al, 2020) 5.78 2.36 14.13 (Manongi et al, 2020) 2.25 1.26 4.02 (Massae et al, 2021) 0.61 0.37 0.98 (Naja et al, 2021) 3.20 1.70 5.90 (Oboro et al, 2022) 4.70 2.99 7.38 (Umuziga et al, 2022) 4.45 1.83 10.84 (Yu et al, 2020) 2.37 1.20 4.66 (Zelalem et al, 2020) 2.07 1.12 3.87 (Zeng et al, 2015) 0.92 0.88 0.97 . The Forest plot indicates the effect of marital status on the incidence of antenatal depression.…”
Section: Resultsmentioning
confidence: 99%